Analysis Of Adolescent Perceptions Of Risky Sexual Behavior - Yusmalia Hidayati; Dita Anggriani Lubis; Dilma'aarij Riski Agustia; Ria Fazelita Br Gultom; Wiwiek Elsada Nainggolan; Fitri Khoiriyah (LPPM Universitas PGRI Sumatera Barat, 2024)
Teenagers are an age group known for their high curiosity. Curiosity and an increase in adolescent sexual hormones during the puberty phase that is not accompanied by appropriate knowledge can lead adolescents to risky sexual behavior. This study aims to analyze teenagers' perceptions of risky sexual behavior. The research design uses a qualitative descriptive design. There were 10 informants in the research (5 class X students and 5 class XI students). Sampling used a porpusive sampling technique in accordance with the inclusion criteria. The research was conducted at SMA Negeri 1 Lhokseumawe using Focus Group Discussion (FGD) guidelines. Analysis of FGD data using interactive analysis techniques. The research results reveal the phenomenon of risky sexual behavior from the informant's perspective as a teenager. Risky sexual behavior is negative behavior from all aspects, it can harm yourself and others. This behavior also has negative physical, psychological and social impacts. It is hoped that the results of this research can be used by health workers and educators in providing education to teenagers and the community to help prevent and overcome risky sexual behavior among teenagers